Cell size induced bias of current density in hypertrophic cardiomyocytes - Lilliu, Elena; Hackl, Benjamin; Zabrodska, Eva; Gewessler, Stefanie; Karge, Tobias; Marksteiner, Jessica; Sauer, Jakob; Putz, Eva M; Todt, Hannes; Hilber, Karlheinz; Koenig, Xaver (Channels (Austin, Tex.), 2024)
Alterations in ion channel expression and function known as "electrical remodeling" contribute to the development of hypertrophy and to the emergence of arrhythmias and sudden cardiac death. However, comparing current density values - an electrophysiological parameter commonly utilized to assess ion channel function - between normal and hypertrophied cells may be flawed when current amplitude does not scale with cell size. Even more, common routines to study equally sized cells or to discard measurements when large currents do not allow proper voltage-clamp control may introduce a selection bias and thereby confound direct comparison. To test a possible dependence of current density on cell size and shape, we employed whole-cell patch-clamp recording of voltage-gated sodium and calcium currents in Langendorff-isolated ventricular cardiomyocytes and Purkinje myocytes, as well as in cardiomyocytes derived from trans-aortic constriction operated mice. Here, we describe a distinct inverse relationship between voltage-gated sodium and calcium current densities and cell capacitance both in normal and hypertrophied cells. This inverse relationship was well fit by an exponential function and may be due to physiological adaptations that do not scale proportionally with cell size or may be explained by a selection bias. Our study emphasizes the need to consider cell size bias when comparing current densities in cardiomyocytes of different sizes, particularly in hypertrophic cells. Conventional comparisons based solely on mean current density may be inadequate for groups with unequal cell size or non-proportional current amplitude and cell size scaling.
Keywords: kardiomegalie; L-type calcium and sodium current density; Myocytes, Cardiac; trans-aortic constriction induced hypertrophy; kardiomyocyty; myši; Mice; Patch-Clamp Techniques; Cardiomegaly; metoda terčíkového zámku; velikost buňky; mužské pohlaví; bias; zvířata; Ventricular and Purkinje myocyte; Cell Size; Animals; cell size; Male; cell capacitance